Detection and Molecular Characterization of Two Little Leaf Phytoplasma Strains Associated with Pepper and Tomato Diseases in Guanajuato and Sinaloa, Mexico - Santos-Cervantes, M E (Plant disease, 2008)
Pepper (Capsicum annuum) and tomato (Lycopersicon esculentum) are important vegetable crops in Mexico. Recently, symptoms associated with phytoplasma diseases such as witches'-broom (shoot proliferation) and little leaf were observed in pepper and tomato fields in central and northwestern Mexico. DNA extracted from symptomatic and asymptomatic plants was used in nested polymerase chain reaction (PCR) assays with primers amplifying 16S rDNA sequences for phytoplasmas. Twenty-four percent of pepper and 49% of tomato samples yielded a nested rDNA product of 1.25 kb. Restriction fragment length polymorphism profiles and sequencing of PCR products allowed classification of the detected phytoplasmas with the aster yellows group (16SrI). Both phytoplasmas, pepper little leaf (PeLL) and tomato little leaf (ToLL), could be included as new members of the aster yellows group because HaeIII and TaqI restriction enzymes discriminated among these phytoplasmas and members of other 16SrI subgroups. PeLL and ToLL phytoplasma sequences were deposited and compared with those in GenBank, and the maximum identity was found with several isolates of 'Candidatus Phytoplasma asteris'. The highest identity (99%) has been observed with tomatillo little leaf phytoplasma and ash witches'-broom phytoplasma. This is the first report of 'Ca. Phytoplasma asteris' associated with pepper and tomato diseases in the Mexican states of Guanajuato and Sinaloa